Human Development: Measurement and Determinants - Poudyal, Niraj (Socio-Economic Development Panorama, 2008)
Human development should be able to encompass all those helpless and hopeless people who are being denied of their basic right of living a dignified life. Human development of a nation depends not only on the economic growth of the nation. Human development depends upon three facets: educational status, standard of living and a health status. Level of income has to do much with other two factors of HDI for low income group of countries. Thus, increasing the level of income for them is much more important than for high income group of countries. High level of inequality not necessarily implies low human development for some countries, but generally HDI tends to be high for the countries with lower inequality. International aid agencies take HDI as a major guidance for deciding how much to be assisted for development Socio Economic Development panorama, Vol. 1, No. 1(2007) pp.1-11